Asynchrony among species and functional groups and temporal stability under perturbations: Patterns and consequences. (8th June 2020) - Huang, Mengjiao; Liu, Xiang; Zhou, Shurong
Abstract: A number of theoretical and empirical studies have demonstrated the effects of perturbations on ecosystem stability. Compensatory dynamics among taxonomic units have been proposed as a major mechanism regulating the temporal stability of biomass production (hereafter 'temporal stability'). However, most studies have focused on the effects of species asynchrony on temporal stability in response to perturbations, and few studies examined how compensatory changes among functional groups affected temporal stability. Here, we conducted a 4‐year functional group removal experiment and a 4‐year experimental warming and nitrogen addition experiment in an alpine meadow of Qinghai‐Tibetan Plateau to investigate the effects of perturbations (functional group removal, experimental warming and nitrogen addition) on temporal stability and the potential mechanisms. In both experiments, temporal stability was positively related to both species and functional group asynchrony. However, species asynchrony and functional group asynchrony responded differently to different types of perturbations. In the removal experiment, although asynchrony among both species and functional groups decreased as more functional groups were removed, structural equation modelling showed that removal of different functional groups could affect temporal stability through altering either species or functional group asynchrony. Warming suppressed temporal stability through decreasing asynchrony among species, while nitrogen addition reduced temporal stability mainly through decreasing functional group asynchrony. Synthesis . Our findings demonstrate the importance of considering compensatory dynamics at different taxonomic levels for predicting temporal stability under anthropogenic perturbations in alpine meadows, and throw light on the importance of protecting both species and functional group richness to maintain temporal stability in the context of global change. Abstract : Our findings demonstrate the importance of considering compensatory dynamics at different taxonomic levels for predicting temporal stability under anthropogenic perturbations in alpine meadows, and throw light on the importance of protecting both species and functional group richness to maintain temporal stability in the context of global change.